То а guestion of teachingof a history of art of modern time: the characteristic of some concept and terms (Pedagogy of Higher and Secondary Education, 2006)
In the article the most widespread determinations an in history of art XX centuries. On the basis of analysis of the special literature and worts of art author interpretation of leading concepts is given.
Keywords: art of XX century; modernism; Ukrainian avant guarde; an criticism terminology